Ethyl 7-chloro-1-cyclopropyl-6-fluoro-8-nitro-4-oxo-1,4-dihydroquinoline-3-carboxylate - Al-Qawasmeh, Raed A. (International Union of Crystallography, 2012)
In the title compound, C(15)H(12)ClFN(2)O(5), molecules are packed in the crystal lattice in a parallel fashion sustained by various C—H⋯O [C⋯O = 3.065 (5)–3.537 (5) Å] and C—H⋯Cl [3.431 (5)–3.735 (4) Å] interactions.